Comparative phytolith analysis of Festuca (Pooideae: Poaceae) species native to Tierra del Fuego, Argentina - Fernández Pepi, María Gabriela (2012)
Festuca L. is one of the most representative native grasses of Tierra del Fuego in the southernmost area of South America. In several patches, however, domestic cattle have overgrazed, causing loss or replacement by exotic and adventitious species. We have carried out a comparative phytolith analysis of Patagonian fescue present in the Province of Tierra del Fuego. Fescue leaves are characterized by the presence of truncated cones, crescents, and sinuate trapezoid elements, predominantly short ones. Fan-shaped, small elongated prismatic, and point-shaped phytoliths, as well as articulated phytoliths originating in vascular and epidermal tissues, were observed less frequently. The most common articulated elements in leaf ashes are long cells and a combination of sinuate trapezoid and long cells or crescents. In inflorescence ash assemblages, long cells with undulate borders in association with crescents or emerging hooks are predominant. We have analyzed the diagnostic and differential characteristics of each species of phytolith assemblages to provide information for further studies on the presence of this species in different past soil samples.